KERAGAMAN JENIS TUMBUHAN BAWAH HUTAN RAWA GAMBUT DI KABUPATEN BANJAR - Dina Naemah; Normela Rachmawati; Eny Dwi Pujawati (Jurnal Hutan Tropis, 2020)
Differences in plant species are determined by genetic and environmental factors. Environmental factors are influenced by humans, so if environmental factors change, it can cause the diversity of growing species to change. Some of the characteristics of peat swamp forest are that it is always wet, has a layer of peat and has a more distinctive plant species because the soil is acidic. This research was conducted in peat swamp forest in Banjar district. This study aims to analyze the structure, composition and diversity index of undergrowth species in peat swamp forests.This research uses the compartmental path method, then analyzed by calculating the INP (Importance Value Index) based on the values of density, frequency and dominance. The study also calculates its diversity index. The results showed 24 species of undergrowth from 14 families. The highest Importance Value index was Papisangan (Ludwigia octovalis) from the Ongraceae family of 41.537%. The distribution value of the species is Banta (Megathyrsus sp) with the density value per hectare is 15.432%, the frequency value of Megathyrsus sp is 14.061% and the largest species dominance value is L. octovalis which is 14.513%. The diversity index for undergrowth was 2.79, meaning that the vegetation in the peat swamp forest had moderate diversity